2021
DOI: 10.4314/ijbcs.v15i3.11
|View full text |Cite
|
Sign up to set email alerts
|

Caractérisation de la pisciculture dans la région du Poro (Nord de la Côte d’Ivoire)

Abstract: Cette étude a été menée afin de faire un diagnostic de l’activité piscicole dans la région du Poro. Elle émane des résultats obtenus à l’issu de 2 mois d’enquêtes (mars et avril, 2014) auprès des pisciculteurs. Il ressort que la pisciculture est semi-intensive et pratiquée par des nationaux. La population de pisciculteurs est dominée par des acteurs dont l’âge est supérieur à 45 ans (75%). Les étangs utilisés sont en dérivation. Tous les acteurs fabriquent leur aliment poisson et éprouvent des difficultés à no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 3 publications
(3 reference statements)
0
2
2
Order By: Relevance
“…In Cameroon, feeds were necessary for fish farming, more than half of the fish farmers feed African bonytongue. Our result was higher than N'dri et al [13] who found in Congo that only 41.70% of fish farmers feed their fish. Most of the fish farmers used imported feed, this result was lower than the result of Tiogué et al [9] where 15% of fish farmers used imported feed while no fish farmers in Congo used imported feed.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…In Cameroon, feeds were necessary for fish farming, more than half of the fish farmers feed African bonytongue. Our result was higher than N'dri et al [13] who found in Congo that only 41.70% of fish farmers feed their fish. Most of the fish farmers used imported feed, this result was lower than the result of Tiogué et al [9] where 15% of fish farmers used imported feed while no fish farmers in Congo used imported feed.…”
Section: Discussioncontrasting
confidence: 81%
“…However, in DRC, 75% to 77.20% of fish farmers were men and the majority of fish farmers are 26 -55 years old [11], Kifufu et al [12]. Our result was not considerable as the results of N'dri et al [13] and Tiogué et al [9] who found respectively that in Congo 88.90% of fish farmers were married as 90% of fish farmers were married in Mbam and Inoubou Division (Centre-Cameroon).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations